2017
DOI: 10.1111/ijfs.13340
|View full text |Cite
|
Sign up to set email alerts
|

Females' attitude and preference for beer: a conjoint analysis study

Abstract: Summary In order to sustain the fast‐expanding beer industry, companies need to attract new female consumers. The main objective of this study was to identify the extrinsic and intrinsic attributes that drive female consumers' purchase of beer. A literature review and focus group (n = 6) were conducted, and six attributes were identified as purchase drivers of beer. These attributes included flavour, appearance (colour), packaging, brand, production methods and beer style. These attributes were used to design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 23 publications
0
28
0
1
Order By: Relevance
“…For all measurements, consumers were forced to choose only one option among those displayed. The second section of the questionnaire explored consumers' preferences for 13 craft beer attributes drawn from the literature (Aquilani et al 2015;Donadini and Porretta 2017;Muggah and McSweeney 2017) addressing the Best-Worst Scaling (BWS) experiment. Socio-demographics characteristics of respondents such as gender, age, household size, education level, occupation, and annual family income were then collected in the end section of the questionnaire.…”
Section: Data Collection and Questionnairementioning
confidence: 99%
See 2 more Smart Citations
“…For all measurements, consumers were forced to choose only one option among those displayed. The second section of the questionnaire explored consumers' preferences for 13 craft beer attributes drawn from the literature (Aquilani et al 2015;Donadini and Porretta 2017;Muggah and McSweeney 2017) addressing the Best-Worst Scaling (BWS) experiment. Socio-demographics characteristics of respondents such as gender, age, household size, education level, occupation, and annual family income were then collected in the end section of the questionnaire.…”
Section: Data Collection and Questionnairementioning
confidence: 99%
“…Over the last decades, the European beer sector has been shaken up by the rising interest of consumers towards beers produced on small scale and slower fermentation process, namely craft beers (Carvalho et al 2018). The creators of this astonishing renaissance, that positively affect the whole beer sector 1 , are mainly the microbreweries 2 (approximately 7900 in Europe, in 2017) (The brewers of Europe 2018) that were able to rethink the product and the sector focusing on high quality, variety, and uniqueness (Calvo-Porral et al 2017;Muggah and McSweeney 2017). Further, they were sensitive to the dynamic consumers' expectations and consumption habits which have generated new business opportunities promptly seized by breweries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Latest research indicates the global alcohol consumption to decline in recent years. However, this decrease has been found to result from the fact that more aware consumers search for novel, special, and valuable products characterized by interesting and diversifi ed fl avors [Podstawski et al, 2017;Muggah & McSweeney, 2017]. For this reason, products that have exceptional sensory attributes and also valuable composition seem to respond to these needs.…”
Section: Introductionmentioning
confidence: 99%
“…Color influences consumer perceptions of flavor, liking, emotions, and overall perception and purchase intent . Chambers and Wolf suggested that ranking tests on visual evaluations might be less prone to fatigue than taste and aroma tests, possibly favoring a joint ranking (1SS) session.…”
Section: Introductionmentioning
confidence: 99%